2017
DOI: 10.1027/1016-9040/a000281
|View full text |Cite
|
Sign up to set email alerts
|

Performance Goals and Task Performance

Abstract: Abstract. Recent years have seen an increased interest in understanding how high-stakes evaluative contexts, which are pervasive in the academic arena, may influence crucial outcomes such as performance and achievement. The salience of grades, as well as the importance to distinguish oneself in the eyes of teachers to have access to valued diplomas, encourages the adoption of performance-approach goals (i.e., the desire to outperform others). Consistent with literature documenting the cognitive costs of high-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 79 publications
0
1
0
Order By: Relevance
“…Mixed findings, on the contrary, emerge from the study of the relation between performance-approach goals and performance. Reviews and meta-analytical results revealed sometimes positive and sometimes weak to nonexistent effects, which also varied as a function of domain-education, work, or sports (Crouzevialle & Butera 2017, Lochbaum & Gottardy 2015, Murayama & Elliot 2012, Payne et al 2007, Van Yperen et al 2014). These meta-analyses are too different to draw any conclusion, but an interesting specification comes from the meta-analysis by Hulleman et al (2010), who coded the phrasing of the items that operationalized achievement goals in the various studies.…”
Section: Achievement Goalsmentioning
confidence: 99%
“…Mixed findings, on the contrary, emerge from the study of the relation between performance-approach goals and performance. Reviews and meta-analytical results revealed sometimes positive and sometimes weak to nonexistent effects, which also varied as a function of domain-education, work, or sports (Crouzevialle & Butera 2017, Lochbaum & Gottardy 2015, Murayama & Elliot 2012, Payne et al 2007, Van Yperen et al 2014). These meta-analyses are too different to draw any conclusion, but an interesting specification comes from the meta-analysis by Hulleman et al (2010), who coded the phrasing of the items that operationalized achievement goals in the various studies.…”
Section: Achievement Goalsmentioning
confidence: 99%
“…For example, high-stakes situations heighten perceived performance pressure, likely producing distracting concerns and worries about one's competence. These concerns and worries are the source of the adoption of performance-avoidance goals (Brodish & Devine, 2009;Jury et al, 2019; see also Crouzevialle & Butera, 2017 for an alternative perspective). On the other hand, situations designed to downplay the importance of winning would likely facilitate the adoption of performance-approach goals; thus such situations would bring adaptive outcomes.…”
Section: Social Interdependence Theorymentioning
confidence: 99%